PENGARUH AKUNTABILITAS PENGELOLAAN KEUANGAN ALOKASI DANA DESA DAN KEBIJAKAN DESA TERHADAP KESEJAHTERAAN MASYARAKAT : (Studi Kasus Pada Desa Lepo Lima Kecamatan Alok Timur Kabupaten Sikka) - Satriani, Yohana; Reo, Hermanus; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2020)
This study aims to determine the effect of accountability in financial management of village fund allocations and village policies on community welfare. This is also done to determine whether the accountability of the financial management of village fund allocations and village policies jointly (simultaneously) affects the welfare of the community. Respondents in this study were 81 people consisting of 35 men and 45 women of various ages and different occupations. The data were analyzed using multiple linear regression analysis by looking at the validity, reliability, normality, multicollinearity, heteroscedasticity, and hypothesis testing with the F test, T test and Multiple Determination Coefficient test. The results showed that the variable financial management accountability for village fund allocation and village policies had an effect on the welfare of the community, as well as the accountability for financial management of village fund allocations and village policies also had a simultaneous effect on community welfare.